Lie symmetries and exact solutions of nonlinear equations of heat conductivity with convection term - Serov, N. I.; Cherniga, R. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
The Lie symmetries of nonlinear diffusion equations with convection term are completely described. The Lie ansatzes and exact solutions of a certain nonlinear generalization of the Murray equation are constructed. An example of the family of non-Lie solutions of the Murray equation is given.